Idârah Ta’lîm al-Lughah al-Arabiyyah li al-Aṭfâl al-Indûnisiyyîn fî Akademiyah al-Nasy’i al-Ṣâliḥ far’ Indonesia - Siti Mufarokah; Abdul Malik Karim Amrullah; Nuril Mufidah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Purpose- This research aims to describe the planning and implementation of Arabic language education in the Academy of Good Youth, Indonesia Branch, and to describe the problems in planning and implementing Arabic language education in the Good Youth Academy, Indonesia branch. Design/Methodologi/Approach- This research uses the qualitative approach using the descriptive analytical method and uses two methods of data collection, namely observation and interview. Findings- The result of this research yielded; (1) that the planning and implementation of Arabic language education for Indonesian children in the Academy of Good Youth, Indonesia branch, was organized by the Arabic language teacher from the educational objectives, educational activities in the classroom and academic assessment; (2) The educational problems in teaching Arabic to Indonesian children at the Good Youth Academy, Indonesia branch, are divided into three types: linguistic problems on the part of the students, linguistic problems on the part of the teacher, and non-linguistic problems, whether on the part of the teacher or on the part of the students. Research Limitation/Implications- With this research, all educational institutions should pay great attention to educational administration in order to provoke success in education.